Rancang Bangun Aplikasi Rentcar Now Pada Rental Mobil Sahabat Purwakarta Berbasis Mobile dengan Metode Prototype - Muhammad Reza Mahendra; Yudhi Raymond Ramadhan; Dadi Iskandar (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
Sahabat Purwakarta Car Rental is a company engaged in services, especially for car rental services in Purwakarta. Ordering and presenting information on car availability is part of the business process activities carried out by Sahabat Purwakarta Car Rental. In the design of the best friend rental car application for mobile-based online ordering, the case study of the friend car rental in Purwakarta, the author uses a prototype software method using the Flutter programming language and uses firebase as the database. The features contained in the rentcar now application at Purwakarta best friend car rental are car availability, car ordering, managing car data, managing order data, and managing report data. The application that was built has been tested using blackbox testing and can run well. In implementing the rentcar now application, it is hoped that ordering and presenting information on car availability will make it easier for consumers and help employees at car rental friends in Purwakarta